Visualizing Cold Spots: TRPM8-Expressing Sensory Neurons and Their Projections - Dhaka, Ajay (J Neurosci, 2008)
Environmental stimuli such as temperature and pressure are sensed by dorsal root ganglion (DRG) neurons. DRG neurons are heterogeneous, but molecular markers that identify unique functional subpopulations are mainly lacking. ThermoTRPs are members of the transient receptor potential family of ion channels and are gated by shifts in temperature. TRPM8 is activated by cooling, and TRPM8-deficient mice have severe deficits in cool thermosensation. The anatomical and functional properties of TRPM8-expressing fibers have not been not comprehensively investigated. We use mice engineered to express the farnesylated enhanced green fluorescent protein (EGFPf) from the TRPM8 locus (TRPM8(EGFPf)) to explore this issue. Virtually all EGFPf-positive cultured DRG neurons from hemizygous mice (TRPM8(EGFPf/+)) responded to cold and menthol. In contrast, EGFPf-positive DRGs from homozygous mice (TRPM8(EGFPf/EGFPf)) had drastically reduced cold responses and no menthol responses. In vivo, EGFPf-positive neurons marked a unique population of DRG neurons, a majority of which do not coexpress nociceptive markers. The fraction of DRG neurons expressing EGFPf was not altered under an inflammatory condition, although an increase in TRPV1-coexpressing neurons was observed. TRPM8(EGFPf) neurons project to the superficial layer I of the spinal cord, making distinct contacts when compared with peptidergic projections. At the periphery, TRPM8(EGFPf) projections mark unique endings in the most superficial layers of epidermis, including bush/cluster endings of the mystacial pads. We show that TRPM8 expression functionally associates with cold sensitivity in cultured DRGs, and provide the first glimpses of the unique anatomical architecture of cold fibers in vivo.